Methodology of Use of Information Technologies in Organization of Physical Education and Sports Classes in Higher Education - Barakaev Bahodir Urakovich (Peerian Journals Publishing, 2022)
The article emphasizes the importance of the use of information technology in the organization of physical education and sports lessons in higher education, the formation of worldview and thinking, the formation of physical, spiritual and moral qualities, the future of physical education and the teaching of physical education and sports.
Keywords: sports; pedagogical technologies; pedagogical process; information